Psychosocial Variables In Occupational Aspirations Of Secondary School Students In Calabar, Nigeria - J. S., Petters; P. N., Asuquo; M., Eyo (Advances in Social Sciences Research Journal, 2015)
This study investigated the influence of some psychosocial factors on occupational aspirations of secondary school students. Specific factors examined in the study were self-concept, gender and parental role. Three hypotheses of the study were tested at 0.05 levels of significance while a questionnaire with a reliability index of 0.815 was used for data collection. Independent t-test statistics was utilized to analyze data from two hundred (200) respondents within the context of Ex-post facto research design. Result of the study revealed a significant influence of the three key variables (self-concept, parental factor and gender) on occupational aspirations of respondents in the study. Based on the findings, it was recommended that occupational information should be made available to young people as early as in the primary school years so as to exert positive moderating influence on their aspirations with a view to avoiding wrong occupations that do not reflect their unique needs, interests and abilities.